The effect of vanillin on the oxidative stability of palm olein - Mohd Azriyuddin, Fatin Nadzirah; Ahmad, Mohammad Norazmi; Omar, Muhammad Nor; Abdullah, Erna Normaya (The Malaysian Analytical Sciences Society, 2019)
The existence of unsaturated fatty acids in palm olein contributes to the oil’s degree unsaturation and reduces the oil’s oxidative stability when it is exposed to atmospheric oxygen and heat. The purpose of this research was to study the effect of vanillin on improving the oxidative stability of palm olein. 1% of vanillin was incorporated into palm olein and the sample was heated at 90 C in an oven for 200 hours. Samples were collected at 0 hours, 50 hours, 100 hours, 150 hours and 200 hours heating prior to analysis using a thermal oxidative stability test including iodine value test, peroxide value test, Fourier transform infrared (FTIR) spectroscopy and thermogravimetric analysis (TGA). The results obtained were compared with the result of palm olein without antioxidant (blank). The results showed that the presence of vanillin in palm olein reduced the autoxidation process and increased the oxidative stability of palm olein by 16.10%, 46.51% and 25.00% based on the peroxide value, absorbance of the infrared spectrum and thermogravimetric sample’s weight gain per cent, respectively.